Sutrisno Effect of Clay Powder Composition on the Tensile Strength and Burn Resistance Properties of Composite Materials - sutrisno, sutrisno -; Salim Subarkah; Nur Chandra Dana Agusti; Gatot Soebiyakto (Universitas Muhammadiyah Metro, 2024)
Composite materials are developing very rapidly. Composite materials are widely used in the automotive industry. Composite materials used in industry are required to have burn resistance. In transportation service regulations, it has been suggested that this material must be burnt-resistant to reduce the high risk. In this research, additional materials were used to make composite materials. The extra material is clay, which is obtained from grinding red bricks. The clay grain size is mesh 200. The variations used are 0:2:88; 3:9:88: 6:6:12; 9:3:88; 12:0:88 (clay, fiber, polyester resin: %). This research aims to determine composite materials' tensile strength and burn resistance. The method used is printing specimens using the hand layup method. The tests carried out were tensile tests, burn tests, and SEM photos. The research results show that at a composition of 0% clay, the tensile strength is 55.65 MPa. The maximum tensile strength at a percentage of 3% clay is 58.67 MPa. The tensile strength decreases at percentages of 6, 9, and 12 clay. Maximum burn resistance at a percentage of 12% clay. The smaller the clay percentage, the higher the burning speed. From the test results, the percentage suitable for use in industry is 3% clay and 9% fiber. This material has tensile strength that meets standards and good burn resistance.